Symptomatic Hypoglycemia Related to Inappropriately High IGF-II Serum Levels in a Patient with Desmoplastic Small Round Cell Tumor - Williams Fernandes Barra; Gilberto Castro; Ana Oliveira Hoff; Sheila A. C. Siqueira; Paulo M. Hoff (Case Reports in Medicine)
A 45-year old man was diagnosed with desmoplastic small round cell tumor (DSRCT) with involvement of the peritoneum and pelvis. Disease progression was observed despite systemic chemotherapy. Six months after diagnosis, he developed severe hypoglycemia presented with seizures. He received intravenous glucose infusion and hydrocortisone with poor glycemic control, but with seizures resolution. The investigation excluded insulinoma, adrenal, liver and GH deficiencies. Laboratory showed slight rise of IGF-II and significant increase of the ratio IGF-II : IGF-I, which is pathognomonic of non-islet cell tumor hypoglycemia (NICTH). He received the diagnoses of NICTH related to IGF-II inappropriate production by DSRCT. Despite the attempt to control tumor mass and hypoglycemia, the patient died 9 months after diagnosis. NICTH related to inappropriate IGF-II secretion should be investigated in all cancer patients with refractory hypoglycemia whom insulinoma and other metabolic abnormalities were excluded from.